Sekundärnutzung klinischer Daten - Rechtliche Rahmenbedingungen mit einem Beitrag von Alexander Roßnagel und Gerrit Hornung - Schneider, Uwe K. (MWV Medizinisch Wissenschaftliche Verlagsgesellschaft, 2015)
Medical research is increasingly using data from care. However, this 'secondary use' of treatment data brings with it numerous legal questions. Social and health data are among the most intimate information about a person. This legal opinion provides for the first time a detailed overview of the specific legal framework for the secondary use of medical data in the individual federal states, which also takes into account the different sponsorship and legal form of the treating institution. The analysis provides researchers and other stakeholders in the health sector with guidance in the legally compliant handling of medical treatment data. The book also contains a supplementary report, which represents the legal framework for the secondary use of the data managed via the electronic health card in accordance with Section 291a Social Code Book V.